The Importance of Internal Representations in the Mere Exposure Effect - Inoue, Kazuya (The Japanese Journal of Mental Imagery, 2020)
The mere exposure effect is a phenomenon in which repeatedly presented stimulus are evaluated positively than unrepeated stimuli. The purpose of this article is to discuss the importance of internal representation in the mere exposure effect. At first, I briefly reviewed previous studies of the mere exposure effect in the viewpoint of a perceptual fluency model. Then, I introduced the classical and recent studies showing the importance of internal representation in the mere exposure effect. Finally the importance of internal representations were discussed based on our recent study indicating the mere exposure effect for visual image.